Comparison of Allele Frequency of Uromodulin Gene rs13333226 and rs13333144 in a Sample of Iraqi Patients on Dialysis - Albayati, Ahmed Saad; Al Jowari, Suha Abdulkhaliq (Iraqi Journal of Science, 2023)
Chronic kidney disease (CKD) is a major public health concern around the world. UMOD gene variants are linked to a higher incidence of hypertension and CKD in the general population. This study aimed to investigate the role of uromodulin rs13333226 and rs13333144 genes association with chronic kidney disease.The study samples were divided into two groups. The first group included 100patient samples and 70 chosen among them were under the dialysis and had kidney failure aged between 18-88 years old. The second group included 30 samples from healthy individuals who were used as a control. One of the ways used to identify the genotype is the tetra-primers amplification refractory mutation system–polymerase chain reaction (ARMS–PCR). Regarding the results of SNP (rs13333226 and rs13333144), the genotypes GG (OR=150.3), and AA (OR=0.01) for rs13333226. The genotypes GG (OR=0.02) and TT(OR=140.4) for rs13333144 when comparing between patients and control (P≤ 0.01), they were observed when the odds ratio is less than 1 means they are preventive factors, while OR more than 1 means the risk increase (P≤ 0.01). It was concluded that there was an association between SNP (rs13333226 and rs13333144) and uromodulin in kidney diseases. Where genotype GG) rs13333226) and TT (rs13333144) represents a risk factor and AA rs13333226 and GG rs13333144 represents a protective factor.